Impact of Climate Risk on Financial Sector Stability of the Selected SADC Countries - Masunda, Shylet (International Journal of Economics and Financial Issues, 2025)
The study investigates the impact of climate risk on the financial sector stability of the selected SADC countries in the context of Angola, Malawi, Mozambique, Madagascar, Namibia, Tanzania, Eswatini, the Democratic Republic of Congo, South Africa, and Zambia. Countries chosen for this study face similar climate-related shocks, such as rising annual carbon dioxide emissions, affecting their agro-based economies and the real sector. The study employed Panel Ordinary Least Squares (POLS), Panel-Corrected Standard Errors (PCSE) and Feasible Generalised Least Squares (FGLS) models to estimate the long-run parameters of climate risks' impact on the region's financial sector stability. The results show that climate risk negatively affects financial stability while positively increasing lending activities. The study recommends that SADC countries expand government-guaranteed bank credit schemes targeting capital projects needed to facilitate the transition to green energy sources and incentivise targeted green investments, particularly green bonds, carbon credits, and green banking, to enhance green growth and financial sector resilience.